Republic of Armenia Public Expenditure Review : Expanding the Fiscal Envelope - World Bank Group (Washington, DC, 2015)
Armenia's small revenue and spending envelopes limit the government's ability to influence the economy, even while its influence through laws, rules, and regulations is significant. The government has an important role to play to reduce poverty and boost shared prosperity, and needs fiscal space. This public expenditure review (PER) analyzes and provides recommendations for the different dimensions of expanding the fiscal envelope. There are three ways of creating fiscal space: the first is higher tax revenue mobilization (through better administration and enforcement of existing taxes, higher tax rates, or new taxes on previously untaxed goods and services or incomes), second, lower spending on less productive programs, and third, an increase in the effectiveness of spending, that is, a higher output of the things the government wants (efficient administration, human capital, services for the population) for a given level of spending. The report highlights Armeniaapos;s limited fiscal envelope, and points out that key areas, such as education, health, and road transport, had been consistently underfunded. It suggests that revenue needs to be significantly improved, and the government will have to revisit its expenditure priorities to create the spending headroom needed to at least maintain the spending level in these areas. The structure of the report is presented as follows: section one gives executive summary. Section two focuses on quantifying fiscal activities. Section three analyzes a number of tax exemptions and loopholes. Section four analyzes ways to improve the impact out of every Armenian dram raised and spent. Section five evaluates in detail the social protection system's performance. Section six accompanies the reforms of Armenia's public service remuneration system.